Overview of emerging research of fungi isolated from the Brazilian environment for the biosynthesis of metal nanoparticles - Sá, Lucas Soares; Morais, Edmilson dos Santos; Jimenez, David Esteban Quintero; Ucella-Filho, João Gilberto Meza; de Oliveira, Alex de Nazaré; Luque , Rafael; Ferreira, Irlon Maciel (Eclética Química, 2026)
Brazil’s rich biological legacy makes it a prime location for studying novel microbes due to its favorable characteristics, which support a wide range of biotechnological applications, including the synthesis of metallic nanoparticles. The number of published studies utilizing fungi from Brazilian habitats for producing metallic nanoparticles has not yet kept pace with this vast microbial richness, making it an underrepresented issue. This review aims to highlight the technological potential of fungus isolated from Brazilian habitats as a biocatalytic source to produce different metallic nanoparticles. A succinct bibliometric diagnosis based on the works in this review is also provided.